The Secret of the Night Train - Bishop, Sylvia (Scholastic Children's Books, 2018)
One small girl; an unexpected detective; a handful of suspects. All aboard the night train, where no one is as they seem! As Max takes off on a thrilling journey across Europe by train, can seh unravel the mystery of a priceless missing diamond and find a way to bing the jewel thief to justice?
Keywords: Mädchen; Detektiv; Dieb; Diamant; Nachtzug; Eisenbahnreise; Kriminalgeschichte; Passenger trains -- Juvenile fiction; Railroad travel -- Europe -- Juvenile fiction; Diamonds -- Juvenile fiction; Jewel thieves -- Juvenile fiction; Jewelry theft -- Juvenile fiction.; Child detectives -- Juvenile fiction; Thieves -- Juvenile fiction; Railroad travel -- Juvenile fiction; Children's stories; Detective and mystery fiction; Children's fiction; Kinderbuch